(untitled) (Bangladesh Journal of Psychology, 2026)
School climate is globally recognized as a key determinant of students’ academic success, psychological well-being, social development, and overall school engagement. But there is no reliable and valid scale in Bangla to measure school climate in Bangladesh. To address this crucial gap, this study aimed to adapt and validate the Bangla Short Form of the School Climate Inventory-Student (BSF ISC-S) in the Bangladeshi context. The translated Bangla version of ISC-S was tested on 1515 secondary school students, selected using a convenience sampling method from various high schools in Bangladesh. Following corrected item-total correlation, item discrimination, and exploratory factor analyses, three items from each of the 10 subscales of ISC-S were retained, establishing the 30-item BSF ICS-S. Then, confirmatory factor analysis confirmed and validated the 10-correlated first-order factor structure of the BSF ICS-S. The BSF ISC-S scale was found to be invariant across gender, developmental period, and educational level. Furthermore, the instrument exhibited acceptable Cronbach’s alpha, test-retest reliability, and robust convergent and divergent validity. These strong psychometric properties indicate that researchers and administrators can use the BSF ICS-S as a valid and reliable instrument to measure positive school climate in Bangladesh. Bangladesh Journal of Psychology, Vol. 26(1), June 2026, pp. 19-40